Membangun Guru Literat Digital: Analisis Kemampuan Literasi Digital Mahasiswa PGSD - Br Ginting, Lea Christina; Magistra, Ari Arasy (Universitas Pendidikan Indonesia (UPI), 2024)
The era of society 5.0 demands that everyone needs digital literacy skills. This study aims to find out how students' digital literacy skills are. The research method used is descriptive quantitative. The study population was all students in semester 2 of the Elementary School Teacher Education Study Program, Faculty of Education, Indonesian University of Education for the 2023/2024 academic year, totaling 210 people. The research sample was 74 people obtained by using simple random sampling technique. Data was collected using a digital literacy skills questionnaire. Data analysis techniques using descriptive statistics. The results of the study showed that score respondents were 89,2% on functional skills and beyond, 40,2% students were difficult to find and select information and were good on the other six aspects of digital literacy. Based on the results of data analysis, it was concluded that the digital literacy abilities of students of the Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Indonesian University of Education were in the